Effects of autophagy inhibitor 3-Methyladenine on ischemic stroke: A protocol for systematic review and meta-analysis - Zhang, Ao (Medicine (Baltimore), 2021)
BACKGROUND: Ischemic stroke is a huge threat to human health globally. Rescuing neurons in the ischemic penumbra (IP) is pivotal after the onset of ischemic stroke, and autophagy is essential to the survival of IP neurons and the development of related pathological processes. As the most common autophagy inhibitor, 3-Methyladenine (3-MA) is widely used in studies related to the mechanism of neuronal autophagy in ischemic stroke; however, there is no consensus has been reached on its effects of neuroprotection or neurodamage, which hinders the development and clinical application of autophagy-targeted therapy strategies for the treatment of ischemic stroke. METHODS: We will search the following electronic bibliographic databases: PubMed, EMBASE, Scopus, Science Direct, and Web of Science. Participant intervention comparator outcomes of this study are as flowing: P, animal models of ischemic stroke; I, received 3-MA treatment merely; C, received only vehicle or sham treatment, or no treatment; O, Primary outcomes are infarct volume; neuro-behavioral scores. Secondary outcomes are cerebral blood flow, blood–brain barrier permeability, cerebral hemorrhage, brain water content. Review Manager 5.3 and Stata 15.1 will be used in data analysis. The characteristics of the studies, the experimental model, and the main results will be described, the quality assessment and the risk of bias assessment will be conducted. A narrative synthesis will be made for the included studies. Besides, if sufficient qualitative data is available, a meta-analysis will be conducted. I(2) statistics will be used to assess heterogeneity. DISCUSSION: This systematic review and meta-analysis of the autophagy inhibitor 3-MAs effects on animal models of ischemic stroke can help us to understand whether inhibiting autophagy brings protection or damage to IP neurons; in addition, it also helps to clarify the specific role of autophagy in cerebral infarction. Therefore, this study can provide evidence for the future development of therapy strategies targeting autophagy and bring more hope to patients with ischemic stroke. PROSPERO REGISTRATION NUMBER: CRD42020194262.